Neonatal Brucellosis: Two Cases with Two Different Transmissions - İlke Mungan Akın; Özlem Kalaycık Şengül; Sibel Sevük Özümüt (Güncel Pediatri)
Brucellosis remains as an endemic infection of humans in many parts of the world; Latin America, Asia including Middle East and Mediterranean region including Turkey. Neonatal brucellosis is very rare and clinical manifestations as well as transmission route are not well-defined. The neonate can be either infected transplacentally, or by ingestion of mother’s secretions and blood during delivery, or by ingestion of breast milk. Here, we present two cases with two different transmission route and clinical findings. First case is a premature infant born after 31 weeks of gestation and hospitalized for respiratory distress in addition to hepatosplenomegaly and leukocytosis. Brucella species were isolated from the initial blood culture obtained just after birth. Clinical and laboratory findings improved with decreased ventilatory support after replacement of antibiotherapy with trimethoprim-sulfamethoxazole (TMP-SMX) and rifampicin. Second case was a 28 days old, term infant. Her sibling was diagnosed as brucellosis and during evaluation of the family members, her mother was found to have brucellosis just before delivery. Initial evaluation of the baby after birth was totally normal. Beside medical advice, she was breastfed and in the 4th week of life she was found to have leucopenia and neutropenia, and brucella tube agglutination test turned to be positive. After antibiotherapy, laboratory findings were normalized. Breastfeeding was ceased during the treatment periods of both mothers. Both families were from rural regions of Turkey, who were using unpasteurized dairy products. Both patients were treated with TMP-SMX and rifampicin for 6 weeks without any complication. Brucella spp must be sought as a causative agent in the differential diagnosis of intrauterine and neonatal infections in endemic countries. Family members of patients from rural areas of the country must be questioned about traditional food consumption, as findings of neonatal brucellosis are various and vague.